Two-lined spittlebug, Prosapia bicincta (Say) (Insecta: Hemiptera: Cercopidae) - Carol Wyatt-Evens; Adam Dale (EDIS)
The two-lined spittlebug, Prosapia bicincta (Say), belongs in the insect order, Hemiptera, which includes the hoppers, scales, and aphids. Prosapia bicincta is in the family Cercopidae, the froghoppers or spittlebugs. This name is earned from their impressive leaping ability that allows them a quick exit when threatened or disturbed. The common name, two-lined spittlebug, describes the two prominent and parallel lines crossing each wing as well as the protective foamy mass secreted by the immature stages while feeding. This insect is an intermittent pest of warm-season turfgrasses and a few ornamental plant species in urban settings. Prosapia bicincta is also an agricultural pest in pasture grasses. This document provides an in-depth synopsis of this insect's biology, identification, and management.